The Role of the Russian Language in the Economic Integration of the Republic of Uzbekistan (Texas Journal of Philology, Culture and History, 2026)
Currently, in the system of higher technical education, teaching the Russian language as an important element of general and professional culture and a means of professional communication has acquired particular relevance. Difficulties in mastering a new (Russian) language are associated with the student’s adaptation to another culture, customs, traditions, history, and values of another people.